Enhancement of 5-aminolevulinic acid-induced photodynamic therapy by a bioadhesive polymer - Shu-Fang Chang; Yu-Tsai Yang; Wei-Ling Li; Che-Tong Lin; Tsuimin Tsai (Elsevier, 2010)
Using a topical formulation of 5-aminolevulinic acid (ALA), a mediated photodynamic therapy (PDT) was developed to treat oral precancerous and cancerous lesions. Several clinical results demonstrated that this special ALA preparation containing Carbopol 971P (CP971P), a bioadhesive polymer, resulted in a satisfactory PDT effect. It is believed that this PDT efficacy may be due to the increased bioadhesion of the preparation at the treatment site. We investigated whether there was a beneficial effect of CP971P on ALA PDT in vitro. Materials and methods: CP971P was co-incubated with ALA in a cell culture system. The effect of CP971P was evaluated by monitoring the uptake of ALA, the fluorescence intensity of protoporphyrin IX, and the cell survival rate. Results: The polymer was found to enhance the fluorescence intensity of protoporphyrin IX and the subsequent PDT effect when concurrently dosed with ALA. Conclusion: Our results showed that a formulation of ALA containing C971P could provide a better ALA PDT effect in cancer treatment.